Optimasi Penyerapan Malachite Green Menggunakan C-Sinamalkaliks[4]Resorsinarena Hasil Sintesis Sebagai Adsorben - Dewi Fortuna Khairil; Sri Benti Etika (Departemen Kimia FMIPA UNP, 2022)
Malachite green is a synthetic dye that is widely used in the textile industry. Textile industry waste that is not treated properly can cause pollution of the aquatic environment. The threshold value for the permissible concentration of malachite green in the water is 0,01 ppm. The adsorption method is one of the alternative method used to remove dye waste. This study used the batch method which aims to determine the optimum absorption conditions and maximum absorption capacity of malachite green using CSKR. In this study, treatment was carried out using variations in pH and concentration. The results of this study obtained that the optimum absorption capacity occurred at pH 3 and a concentration of 200 mg/L. This CSKR can be used in the absorption of malachite green dye.